All-solid-state lithium battery and method for manufacturing the same

The all-solid-state lithium battery design with a lithium metal anode, lithium lanthanum zirconium tantalum oxide electrolyte, and a lithium nitride alloy interface addresses the safety and cycle life issues of conventional batteries, achieving high energy density and extended cycle life.

JP2025009648APending Publication Date: 2025-01-20CPC CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023149669
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-06
Filing Date
2023-09-14
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Conventional liquid lithium batteries have low energy density and pose safety risks, while all-solid-state lithium batteries suffer from a short cycle life.

Method used

An all-solid-state lithium battery design incorporating solid lithium metal, lithium lanthanum zirconium tantalum oxide as the solid electrolyte, and a bonding interface region containing lithium nitride and a lithium alloy, formed through a manufacturing process involving the mixing and heating of lithium metal and nitride metal to create a molten state, followed by an in-situ reaction with lithium lanthanum zirconium tantalum oxide.

Benefits of technology

The resulting battery achieves high energy density with low risk of fire or explosion and significantly improved cycle life, maintaining discharge capacity and Coulombic efficiency after multiple charge-discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009648000001_ABST
    Figure 2025009648000001_ABST
Patent Text Reader

Abstract

To provide a solid-state lithium battery with a high energy density, a low risk, and an excellent cycle life.SOLUTION: In the all-solid-state lithium battery, the positive electrode of the all-solid-state lithium battery includes a solid-state lithium metal and the solid-state electrolyte of the all-solid-state lithium battery includes lithium lanthanum zirconium tantalum oxide, and the joint interface region of the positive electrode and the solid-state electrolyte includes at least lithium nitride and lithium alloy.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state lithium battery and a manufacturing method thereof, and in particular to an all-solid-state lithium battery containing solid lithium metal and lithium lanthanum zirconium tantalum oxide, in which a bonding interface region between the solid lithium metal and the lithium lanthanum zirconium tantalum oxide contains lithium nitride and a lithium alloy, and a manufacturing method thereof. [Background technology]

[0002] In recent years, the development of electric vehicles has become a mainstream trend in the automotive industry, and electric vehicles use liquid lithium batteries as their energy source. However, traditional liquid lithium batteries have low energy density and are prone to fire and explosion in high-temperature environments.

[0003] In order to overcome the low energy density and safety risks of conventional liquid lithium batteries, the development of all-solid-state lithium batteries is currently underway. All-solid-state lithium batteries have a high energy density and no risk of fire or explosion, but they have a problem of short cycle life. The cycle life refers to the total number of times a battery's capacity is discharged from 100% to 0% and then recharged from 0% to 100%. A short cycle life of a battery means that the battery can only be charged and discharged a small number of times. Therefore, there is a demand for a manufacturing method that improves the cycle life of all-solid-state lithium batteries. Summary of the Invention [Problem to be solved by the invention]

[0004] Therefore, an object of the present invention is to provide a solid-state lithium battery that can solve the problem of short cycle life of solid-state lithium batteries. [Means for solving the problem]

[0005] The technical means used by the present invention to solve the conventional technical problems provides an all-solid-state lithium battery, characterized in that the anode of the all-solid-state lithium battery comprises solid lithium metal, the solid electrolyte of the all-solid-state lithium battery comprises lithium lanthanum zirconium tantalum oxide, and the bonding interface region between the anode and the solid electrolyte comprises at least lithium nitride and a lithium alloy.

[0006] In one embodiment of the present invention, there is provided an all-solid-state lithium battery, wherein the lithium alloy is a lithium gallium alloy.

[0007] In one embodiment of the present invention, there is provided an all-solid-state lithium battery, wherein the cathode of the all-solid-state lithium battery is lithium iron phosphate or an oxide thereof.

[0008] In addition, another technical means used by the present invention to solve the conventional technical problems is a method for manufacturing an all-solid-state lithium battery, comprising: a first step of mixing and heating lithium metal and metal nitride as a material for the anode of the all-solid-state lithium battery to form a molten lithium metal nitride alloy; a second step of placing lithium lanthanum zirconium tantalum oxide as a material for the solid electrolyte of the all-solid-state lithium battery on the surface of the molten lithium metal nitride alloy to generate an in-situ reaction; and a third step of lowering the temperature of the molten lithium metal nitride alloy, so that the junction interface region between the molten lithium metal nitride alloy and the lithium lanthanum zirconium tantalum oxide contains lithium nitride and lithium alloy, and the junction interface region between the anode and the solid electrolyte of the all-solid-state lithium battery contains at least lithium nitride and lithium alloy.

[0009] As a result, the temperature of the molten lithium metal nitride alloy (hereinafter referred to as Li-Ga-N) and lithium lanthanum zirconium tantalum oxide (hereinafter referred to as LLZTO) is lowered so as to form them into a solid form, and the solid Li-Ga-N and LLZTO are formed into a physical form in which they are tightly bonded to each other, thereby obtaining a Li-Ga-N / LLZTO material composed of a solid electrolyte layer and an anode layer, which is further combined with a cathode layer to obtain an all-solid-state lithium battery.

[0010] In one embodiment of the present invention, there is provided a method for producing an all-solid-state lithium battery, wherein in the first step, a weight ratio of the metal nitride to the lithium metal is 0.01:1 to 0.03:1.

[0011] In one embodiment of the present invention, there is provided a method for producing an all-solid-state lithium battery, wherein the heating temperature in the first step is 400 to 450°C.

[0012] In one embodiment of the present invention, there is provided a method for producing an all-solid-state lithium battery, wherein in the second step, the in-situ reaction is carried out for 10 to 20 minutes. Effect of the Invention

[0013] The all-solid-state lithium battery according to the technical means used in the present invention has high energy density, low risk, and excellent cycle life. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a diagram showing the results of electrochemical impedance spectroscopy of an all-solid-state lithium battery in one embodiment according to the present invention. [Diagram 2] FIG. 2 is a graph showing the trend of the voltage of an all-solid-state lithium battery in one embodiment according to the present invention. [Diagram 3] FIG. 2 is a diagram showing the results of secondary ion mass spectrometry of an all-solid-state lithium battery in one embodiment according to the present invention. [Figure 4]FIG. 2 is a diagram showing the electrochemical cycle of an all-solid-state lithium battery in one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described with reference to Figs. 1 to 4, however, the description does not limit the embodiment of the present invention, but is merely one example of the present invention.

[0016] An all-solid-state lithium battery according to one embodiment of the present invention is characterized in that an anode of the all-solid-state lithium battery contains solid lithium metal, a solid electrolyte of the all-solid-state lithium battery contains lithium lanthanum zirconium tantalum oxide, and a bonding interface region between the anode and the solid electrolyte contains at least lithium nitride and a lithium alloy.

[0017] In one embodiment of the all-solid-state lithium battery according to the present invention, the lithium alloy is a lithium gallium alloy.

[0018] In one embodiment of the all-solid-state lithium battery according to the present invention, the cathode of the all-solid-state lithium battery is lithium iron phosphate or its oxide.

[0019] A manufacturing method of an all-solid-state lithium battery according to one embodiment of the present invention is characterized by comprising: a first step of mixing and heating lithium metal and metal nitride as materials for the anode of the all-solid-state lithium battery to form a molten lithium metal nitride alloy; a second step of placing lithium lanthanum zirconium tantalum oxide as a material for a solid electrolyte of the all-solid-state lithium battery on a surface of the molten lithium metal nitride alloy to generate an in-situ reaction; and a third step of lowering the temperature of the molten lithium metal nitride alloy, so that the junction interface region between the molten lithium metal nitride alloy and the lithium lanthanum zirconium tantalum oxide contains lithium nitride and lithium alloy, and the junction interface region between the anode and the solid electrolyte of the all-solid-state lithium battery contains at least lithium nitride and lithium alloy.

[0020] In one embodiment of the method for producing an all-solid-state lithium battery according to the present invention, the metal nitride in the first step is gallium nitride.

[0021] In one embodiment of the method for producing an all-solid-state lithium battery according to the present invention, the weight ratio of the metal nitride to the lithium metal in the first step is 0.01:1 to 0.03:1.

[0022] In one embodiment of the method for producing an all-solid-state lithium battery according to the present invention, the heating temperature in the first step is 350 to 500°C.

[0023] In one embodiment of the method for producing an all-solid-state lithium battery according to the present invention, the heating temperature in the first step is 400 to 450°C.

[0024] In the method for producing an all-solid-state lithium battery according to one embodiment of the present invention, the in-situ reaction in the second step is carried out for 10 to 20 minutes.

[0025] In this embodiment, first, 0.02 g of gallium nitride and 1 g of lithium metal are weighed. That is, it is preferable that the weight ratio of gallium nitride to lithium metal is 0.02:1, and the weight ratio of gallium nitride to lithium metal is adjusted within the range of 0.01:1 to 0.03:1. In addition, the weight ratio of gallium nitride to lithium metal can be adjusted arbitrarily depending on the manufacturing convenience. The above-mentioned gallium nitride and lithium metal are placed on a stainless steel plate, and the stainless steel plate is placed in an oven filled with a nitrogen atmosphere and heated to 450°C. By filling the oven with a nitrogen atmosphere, it is possible to prevent the nitrogen atoms of gallium nitride from being separated.

[0026] The heating temperature of the gallium nitride and lithium metal can be within a range of 350 to 500° C., and is preferably within a range of 400 to 450° C. As a result, the gallium nitride and lithium metal are heated so as to form molten gallium nitride and molten lithium metal.

[0027] The molten gallium nitride and molten lithium metal are then mixed uniformly to form a molten lithium / gallium nitride alloy.

[0028] The molten lithium / gallium nitride alloy can be used directly in the subsequent manufacturing process of the all-solid-state lithium battery, or the molten lithium / gallium nitride alloy can be cooled to room temperature for storage to form a solid-state lithium / gallium nitride alloy, and then reheated to 450°C to form a molten lithium / gallium nitride alloy when in use.

[0029] Then, lithium lanthanum zirconium tantalum oxide is provided. In this embodiment, LLZTO is produced by the following method. First, lithium hydroxide, lanthanum oxide, zirconium oxide, and tantalum oxide are prepared, and the weight ratio (g) of the precursor is 6.00:32.99:7.27:3.73. In the lithium lanthanum zirconium tantalum oxide, lithium oxide, lanthanum oxide, zirconium oxide, and tantalum oxide are provided in an atomic molar ratio of lithium:lanthanum:zirconium:tantalum=7.425:3:1.75:0.25.

[0030] Next, the lithium oxide, lanthanum oxide, zirconium oxide, and tantalum oxide mentioned above are placed in a ball mill (Retsch. PM100), 100 ml of 99.99% isopropanol is added to the can of the ball mill, and the ball mill is operated at a rotation speed of 300 rpm / min for 12 hours to mix the materials uniformly and form a suspension.

[0031] Finally, the suspension was taken out of the ball mill and heated and dried in an aluminum oxide crucible at 70 ° C for 12 hours, and then sintered at 900 ° C for 12 hours to produce 50 g of cubic LLZTO, whose molecular formula is Li 6.75 La3Zr 1.75 Ta 0.25 O 12 It is.

[0032] The obtained cubic LLZTO is placed in the ball mill and ball milled at a rotation speed of 300 rpm / min for 12 hours to produce LLZTO powder.

[0033] The LLZTO powder is filled into a tablet-shaped mold with a diameter of 12 mm, and a pressure of 20 tons is applied to the tablet-shaped mold for 1 minute. After demolding, raw LLZTO tablets with a diameter of 12 mm and a thickness of 3 mm are obtained.

[0034] The obtained raw processed tablet is placed in an aluminum oxide crucible, the surface of the raw processed tablet is covered with LLZTO powder of twice the weight of the raw processed tablet, a lid is placed on the crucible in which the raw processed tablet is placed, and this crucible is placed in another large crucible and a lid is placed on it. The large crucible is heated to 900°C, and the raw processed tablet is subjected to a sintering reaction in an environment of 900°C for 4 hours, and then further heated to 1100°C, and the raw processed tablet is subjected to a sintering reaction in an environment of 1100°C for 12 hours, thereby obtaining an electrolyte tablet in the solid form of LLZTO.

[0035] The solid-form electrolyte tablet of LLZTO is placed on the surface of a lithium / gallium nitride alloy that is heated to a molten state, and an in-situ reaction is carried out for 15 minutes in an environment of 450°C.

[0036] The time for the in situ reaction can be within a range of 10 to 20 minutes, and is preferably within a range of 13 to 17 minutes.

[0037] The temperature of the in-situ reaction, ie, the lithium / gallium nitride alloy in the molten state, can be within the range of 350 to 500°C, and is preferably within the range of 400 to 450°C.

[0038] By carrying out an in-situ reaction under the above-mentioned conditions, a bonding interface is formed between the lithium / gallium nitride alloy (hereinafter referred to as Li-Ga-N) and the solid electrolyte tablet of LLZTO. That is, the Li-Ga-N alloy forms an anode layer on the surface of the solid electrolyte tablet of lithium lanthanum zirconium tantalum oxide.

[0039] Finally, the temperature of the molten Li-Ga-N alloy is reduced to form a solid Li-Ga-N alloy, and the solid Li-Ga-N and LLZTO are tightly bonded to each other in a physical form, thereby obtaining a Li-Ga-N / LLZTO material consisting of a solid electrolyte layer and an anode layer, which is then combined with a cathode layer to form an all-solid-state lithium battery.

[0040] The Li-Ga-N / LLZTO material according to this embodiment has a surface in which molten Li and GaN are heated and decomposed to form Li3N and Li-Ga alloys, which can maintain the interface stability between Li-Ga-N and LLZTO and suppress the formation of lithium metal dendrites (i.e., the precipitation of lithium metal dendrites), thereby avoiding the risks of low safety, short cycle life, and malfunction caused by the formation of dendrites in lithium batteries.

[0041] [Electrochemical impedance spectroscopy of all-solid-state lithium batteries]

[0042] First, a conventional lithium / lithium lanthanum zirconium tantalum oxide / lithium all-solid-state symmetrical (i.e., both the cathode and anode contain lithium metal) lithium battery (hereinafter referred to as Li / LLZTO / Li battery) is manufactured, and then, using the Li-Ga-N / LLZTO material of this embodiment, a lithium-gallium nitride / lithium lanthanum zirconium tantalum oxide / lithium-gallium nitride all-solid-state symmetrical (i.e., both the cathode and anode contain lithium-gallium nitride material) lithium battery (hereinafter referred to as Li-Ga-N / LLZTO / Li-Ga-N battery) having a different lithium-gallium nitride doping ratio is manufactured. In this analysis, the Li / LLZTO / Li battery was designated as the control group, the 1 wt% Li-Ga-N / LLZTO / Li-Ga-N battery was designated as experimental group 1, the 3 wt% Li-Ga-N / LLZTO / Li-Ga-N battery was designated as experimental group 2, the 5 wt% Li-Ga-N / LLZTO / Li-Ga-N battery was designated as experimental group 3, and the 7 wt% Li-Ga-N / LLZTO / Li-Ga-N battery was designated as experimental group 4.

[0043] Next, an electrochemical impedance spectroscopy (EIS) analyzer PGSTAT30 (Autolab) was used to perform an AC impedance test by connecting the cathode and anode of the EIS analyzer to the anode and cathode of the batteries of the control group and experimental groups 1 to 4, respectively. The AC frequency range of the EIS analyzer was set to 1M to 0.1Hz, that is, the analysis frequency was set to 1M to 0.1Hz. Thus, electrochemical impedance spectroscopy was performed on the control group and experimental groups 1 to 3, and the analysis results of the interface impedance are shown in Figure 1 and Table 1.

[0044] [Table 1]

[0045] As shown in FIG. 1 and Table 1, experimental set 1 had the lowest 21 (ohm cm 2 ) interface impedance, while the control set had an interface impedance of 589 (ohm cm2 ), that is, the interface impedance of the experimental set 1 is 1 / 28 of that of the control set. In addition, the experimental sets 2 to 4 also have interface impedances much lower than those of conventional solid-state batteries, proving that different gallium nitrides have the effect of lowering impedance.

[0046] The higher the interface impedance of a solid-state battery, the more difficult it is to achieve sufficient contact between the solid electrolyte and the electrode interface, which increases the energy loss during charging and discharging of the solid-state battery, making it difficult to achieve high-speed charging and discharging. According to the above test, the all-solid-state lithium battery of the present embodiment has better energy transmission efficiency and can achieve high-speed charging and discharging compared to conventional all-solid-state batteries.

[0047] [Voltage trend test of solid-state lithium batteries]

[0048] In this test, a charge / discharge measuring device BAT-750B (manufactured by AcuTech) was used to connect the anode and cathode of the solid-state battery, and a constant positive and negative current of 0.1 mA / cm was applied. 2 The voltage tendency of the Li-Ga-N / LLZTO / Li-Ga-N battery mentioned above is tested, and the cycle of positive and negative constant current is set to 1 hour, and the constant current cycle is continued for 1000 hours to test the voltage tendency of the Li-Ga-N / LLZTO / Li-Ga-N battery during this period. The test results are shown in Figure 2.

[0049] As shown in Figure 2, during the 1000-hour test, the voltage of the Li-Ga-N / LLZTO / Li-Ga-N battery is mainly maintained in a fixed range. According to the above results, even after the Li-Ga-N / LLZTO / Li-Ga-N battery is subjected to constant current cycling for 1000 hours, the Li-Ga-N / LLZTO / Li-Ga-N battery does not become short circuited and the voltage remains constant.

[0050] [Charge and discharge cycle test of solid-state lithium batteries]

[0051] In this test, the Li-Ga-N / LLZTO material according to this embodiment is assembled with a lithium iron phosphate (LFP) cathode to produce a Li-Ga-N / LLZTO / LFP battery. The Li-Ga-N / LLZTO / LFP battery is connected to a charge / discharge measuring device BAT-750B (manufactured by AcuTech) and cycled at a rate of 0·1C in a room temperature environment. The results of this test are shown in Figures 3 and 4.

[0052] As shown in Figures 3 and 4, the Li-Ga-N / LLZTO / LFP battery has a discharge capacity of 150mAh / g (Figure 3) and a Coulombic efficiency, i.e., the percentage of the discharge capacity and charge capacity of the battery, of 96.8% (Figure 4) when the initial charge / discharge cycling test is performed, and the Li-Ga-N / LLZTO / LFP battery has a discharge capacity of 139mAh / g (Figure 4) and a Coulombic efficiency of 91.4% (Figure 4) after 100 cycles of charge / discharge cycling. The above test shows that the all-solid-state lithium battery according to this embodiment can maintain a discharge capacity and Coulombic efficiency close to those at the initial discharge after 100 cycles of charge / discharge cycling.

[0053] As described above, the all-solid-state lithium battery according to the present invention can improve the stability of the interface due to the close contact interface between the anode Li-Ga-N and the solid electrolyte LLZTO, thereby improving the cycle life of the all-solid-state lithium battery. In addition, from the above analysis and test, the all-solid-state lithium battery according to the present invention has a low interface impedance, and can realize high-speed charging and discharging with better energy transmission efficiency compared to conventional all-solid-state batteries. In addition, the all-solid-state lithium battery according to the present invention does not short circuit and maintains a constant voltage even after constant current cycling for 1000 hours. The all-solid-state lithium battery according to the present invention includes Li3N and LiGa alloy, both of which can maintain the interface stability between Li-Ga-N and LLZTO and have the effect of suppressing the formation of lithium metal dendrites. In addition, the all-solid-state lithium battery according to the present invention can maintain the discharge capacity and coulombic efficiency of the battery after 100 cycles of charge and discharge cycling, which are close to those of the battery at the first discharge.

[0054] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. 1. An all-solid-state lithium battery, comprising: an anode of the all-solid-state lithium battery comprising solid lithium metal; a solid electrolyte of the all-solid-state lithium battery comprising lithium lanthanum zirconium tantalum oxide; and a bonding interface region between the anode and the solid electrolyte comprising at least lithium nitride and a lithium alloy.

2. 2. The all-solid-state lithium battery according to claim 1, wherein the lithium alloy is a lithium gallium alloy.

3. 2. The all-solid-state lithium battery according to claim 1, wherein the cathode of the all-solid-state lithium battery is lithium iron phosphate or an oxide thereof.

4. A method for producing an all-solid-state lithium battery, comprising: A first step of mixing and heating lithium metal and metal nitride as materials for the anode of the all-solid-state lithium battery to form a molten lithium metal nitride alloy; A second step of placing lithium lanthanum zirconium tantalum oxide as a material of a solid electrolyte of the all-solid-state lithium battery on the surface of the molten lithium metal nitride alloy to generate an in-situ reaction; a third step of lowering a temperature of the molten lithium metal nitride alloy to contain lithium nitride and a lithium alloy at a bonding interface region between the molten lithium metal nitride alloy and the lithium lanthanum zirconium tantalum oxide, and a third step of containing at least lithium nitride and a lithium alloy at a bonding interface region between the anode and the solid electrolyte of the all-solid-state lithium battery.

5. 5. The method for producing an all-solid-state lithium battery according to claim 4, wherein in the first step, the metal nitride is gallium nitride.

6. 5. The method for producing an all-solid-state lithium battery according to claim 4, wherein in the first step, a weight ratio of the metal nitride to the lithium metal is 0.01:1 to 0.03:

1.

7. The method for producing an all-solid-state lithium battery according to claim 4, wherein in the first step, the heating temperature is 350 to 500° C.

8. The method for producing an all-solid-state lithium battery according to claim 7, wherein in the first step, the heating temperature is 400 to 450°C.

9. The method for producing an all-solid-state lithium battery according to claim 7, wherein in the second step, the in-situ reaction is carried out for 10 to 20 minutes.

Citation Information

Patent Citations

  • Solid-state battery and electric equipment

    CN115207483A

  • Charging method, charging device, and power supply device of lithium-ion secondary battery

    JP2005158285A

  • Layer structure of solid-state battery and manufacturing method thereof

    JP2023510949A